Persepsi Siswa Terhadap Kinerja Guru Bimbingan dan Konseling yang Bersertifikasi Pendidik - Nugroho, Ferry Adji (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
This study aimed to describe the perception of students on teacher performance counseling certified educators (the field of guidance and counseling). the method in this research is descriptive quantitative research. The research was conducted in SMP N 1 Banguntapan, with a population of students of class IX in SMP N 1 Banguntapan with the number of 30 students. Instruments in this study using a questionnaire with data analysis techniques using grouping criteria, moderate, and less. The results obtained in this study concluded that students perceptions of teacher performance guidance and counseling in both categories on the basis of the data categories of each aspect, among others: aspects of personal competence with the number of 14 students (47%), aspects of social competence with number 25 students (83%), and aspects of professional competence by the number of 23 students (77%). This study may provide information to teachers BK to improve performance related to personal competence, social, and professional, so it can be a teacher BK capable of carrying out its duties and responsibilities in providing guidance and counseling services in schools optimally.